Effects of nanoparticle applications on seedling survival and morphological characteristics in Scots pine afforestation - Ayan, Sezgin; Yer Celik, Esra Nurten; Gulseven, Orhan; Yer, Batin Mehmet; Eskiomer, Muhammed (BioResources, 2023)
This study was conducted in the afforestation area, using bare-root 2+0-year-old Scots pine seedlings from Kastamonu. The study aimed to determine the impact of nanoparticle (NP) applications on seedling morphological characteristics and seedling survival success. Three different concentrations (low, medium, high) and four different nanoparticle types [Fe₃O₄, CuO, ZnO, TiO2] were applied to the plant root-dipping method in the study. The effects of NP treatments on seedling height (SH), root collar diameter (RCD), stem fresh weight (SFW), root new weight (RFW), seedling fresh weight (SEFW), root dry weight (RDW), stem dry weight (SDW), seedling dry weight (SEDW), sturdiness quotient (SI), root: shoot ratio (R/S), and seedling survival in the field were evaluated. The study results revealed that NP types significantly affected all seedling variables except RFW, SDW, RDW, and SEDW, and NP doses significantly affected all seedling variables except RFW. The binary interaction effects of NP types and doses had a significant effect on all seedling variables, and higher values were obtained compared to the control treatment. Medium and high NP doses were more effective in seedling growth than low doses; the percentage of seedling survival was 61.4% in the control treatment and 95% in the TiO2-Medium NP treatment combination.
Keywords: scots pine; Seedling morphology; Afforestation; afforestation; Scots pine; Nanoparticles; seedling morphology; nanoparticles; TP248.13-248.65; Biotechnology; 2. Zero hunger; 15. Life on land